High internal phase emulsion as a fat replacer: Effect on physico-chemical properties, microstructure and protein digestibility of processed meat during reheating - Lilan Xu; Yuanqi Lv; Yan Zhao; Yao Yao; Na Wu; Shuping Chen; Yonggang Tu (Poultry Science)
Excessive intake of saturated fatty acids poses health risks, necessitating the development of healthier animal fat substitutes. In this study, high internal phase emulsion (HIPE) stabilized by egg yolk-hydroxypropyl distarch phosphate (EY-HPDSP) complex was used as a fat replacer in processed meat. The effect of fat replacement ratios (0 %, 50 %, 100 %) and reheating core temperature (75 ℃, 85 ℃, 95 ℃) on physico-chemical properties, microstructure and protein digestibility of processed meat was investigated. HIPE addition enhanced the hardness, springiness and L* values, and reduced the cooking loss and TBARs values of the processed meat (P < 0.05). Moreover, the replacement of HIPE significantly increased the protein digestibility and surface hydrophobicity, decreased the free sulfhydryl content and also caused the decreases in the amount of α-helix concomitant with increases in β-sheet, random coil and β-turn contents. When reheated to the core temperatures of 75-85 ℃, the hardness, T22 and A22 and protein digestibility were not significantly affected by 50 % fat substitution. At 95 ℃, the HIPE filled in the matrix underwent destruction that reduced the springiness of fat-reduced meats. This study suggested that HIPE fabricated by EY-HPDSP complex could be a viable fat replacer for processed meat before and reheating.